Role of Information Technology in Implementation of Telemedicine System - Soltanzadeh, Ladan; Taheri, Arezou; Rabiee, Mohammad (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Introduction: Telemedicine is the wide description of providing medical and healthcare services by means of telecommunications. Methodology: A search of electronic databases including Medline, Excerpta Medica Database (EMBASE), Cochrane, and Cumulative Index to Nursing and Allied Health Literature (CINAHL) for relevant papers was performed. All studies addressing the use of telemedicine in emergency medical or pre-hospital care setting were included. Out of a total of 1,230 abstracts that were reviewed, result of 39 articles and 3 books and author ’s experiences were gathered. Findings:Technologies do not only assist medical practitioners and patients receiving treatment, they also benefit perfectly healthy people by providing a wide range of general health assessments. Conclusion: telemedicine is medical services through the use of telecommunications.